Human intersegmental reflexes from intercostal afferents to scalene muscles. Issue 10 (31st August 2016) - McBain, Rachel A.; Taylor, Janet L.; Gorman, Robert B.; Gandevia, Simon C.; Butler, Jane E.
Abstract : New Findings: What is the central question of this study? The aim was to determine whether specific reflex connections operate between intercostal afferents and the scalene muscles in humans, and whether these connections operate after a clinically complete cervical spinal cord injury. What is the main finding and its importance? This is the first description of a short‐latency inhibitory reflex connection between intercostal afferents from intercostal spaces to the scalene muscles in able‐bodied participants. We suggest that this reflex is mediated by large‐diameter afferents. This intercostal‐to‐scalene inhibitory reflex is absent after cervical spinal cord injury and may provide a way to monitor the progress of the injury. Short‐latency intersegmental reflexes have been described for various respiratory muscles in animals. In humans, however, only short‐latency reflex responses to phrenic nerve stimulation have been described. Here, we examined the reflex connections between intercostal afferents and scalene muscles in humans. Surface EMG recordings were made from scalene muscles bilaterally, in seven able‐bodied participants and seven participants with motor‐ and sensory‐complete cervical spinal cord injury (median 32 years postinjury, range 5 months to 44 years). We recorded the reflex responses produced by stimulation of the eighth or tenth left intercostal nerve. A short‐latency (∼38 ms) inhibitory reflex was evident in able‐bodied participants, in ipsilateral and contralateral scalene muscles. This bilateral intersegmental inhibitory reflex occurred in 46% of recordings at low stimulus intensities (at three times motor threshold). It was more frequent (in 75–85% of recordings) at higher stimulus intensities (six and nine times motor threshold), but onset latency (38 ± 9 ms, mean ± SD) and the size of inhibition (23 ± 10%) did not change with stimulus intensity. The reflex was absent in all participants with spinal cord injury. As the intercostal‐to‐scalene reflex did not increase with larger stimulus intensities, it is likely to be mediated by large‐diameter intercostal muscle afferents. This is the first demonstration of an intercostal‐to‐scalene reflex. As the reflex requires intact spinal connections, it may be a useful marker for recovery of thoracic or cervical spinal injury. Abstract :